2013
DOI: 10.1111/joor.12120
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resilient liner and clip attachments for bar‐implant‐retained mandibular overdentures on opposing maxillary ridge. A 5‐year randomised clinical trial

Abstract: This study aimed to compare the influence of resilient liner and clip attachments for bar-implant-retained mandibular overdentures on opposing maxillary ridge after 5 years of denture wearing. Thirty edentulous male patients (mean age 62·5 years) received two implants in the anterior mandible after being allocated into two equal groups using balanced randomisation. After 3 months, implants were connected with resilient bars. New maxillary complete dentures were then constructed, and mandibular overdentures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 21 publications
5
59
0
Order By: Relevance
“…This prosthesis is simple to fabricate, cost effective, and exerts the least surgical damage to the tissues . Different attachment types can be used for such overdentures, including bars of different designs, balls, and magnetic and resilient telescopic attachments …”
mentioning
confidence: 99%
“…This prosthesis is simple to fabricate, cost effective, and exerts the least surgical damage to the tissues . Different attachment types can be used for such overdentures, including bars of different designs, balls, and magnetic and resilient telescopic attachments …”
mentioning
confidence: 99%
“…Residual ridge resorption (RRR) in complete denture (CD) wearers is a continuous, inevitable process and is affected by the type of prostheses that overlay and also oppose the residual ridge . Several studies have shown greater RRR in the anterior maxilla beneath a maxillary CD opposed by a mandibular two‐implant‐retained overdenture (IOD) than in one opposed by a mandibular CD . In contrast, other studies have found no difference in the RRR rate between the two modalities of treatment or an even greater RRR in the case of conventional CD therapy attributable to lack of retention and stability …”
mentioning
confidence: 99%
“…Moreover, these overdentures are indicated for patients with poor bone quality, buccal bone inclination, high lip line, thin mobile mucosa, and insufficient lip support to achieve proper phonetics and esthetics . Maxillary implant overdentures opposing mandibular implant‐retained prostheses may prevent development of degenerative changes of the maxillary ridge (combination syndrome) . Attachment systems used for relating implant‐retained overdentures to underlying implants include splinting (bar‐clip construction with various bar shape designs) and nonsplinting attachments (various ball types, magnets, resilient studs [Locators], and telescopic crowns) …”
mentioning
confidence: 99%